Doped zirconia electrolyte and electrolyte supported SOC unit preparation method

By improving the common precipitation method and multi -layer flow, and the co -sintering process, the problem of component analysis and complex sintering process in the process of doping oxide electrolytic materials during the preparation process is solved. The stability of the craftsmanship.

CN119381485APending Publication Date: 2025-01-28CHENGDU YUNHAI XINGHE TECHNOLOGY SERVICE CO LTD

Patent Information

Application Number
CN202411638033.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-16
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

During the preparation process, existing doped zirconia electrolyte materials have complex and high cost problems in component segregation and sintering processes, resulting in easy breakage of units and unstable process.

Method used

Adopt improvement co -precipitation method, to dissolve the third set of doped materials in the water -free ethanol and anchor the dispersant, combine with spray drying and multi -layer flow, and sintering process to prepare a uniform electrolyte powder and Electrolyte supports SOC unit.

Benefits of technology

Effectively solve the problem of component bias, simplify the sintering process, reduce the unit damage rate, and improve the repetitiveness and reliability of the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005137574870000011
    Figure HDA0005137574870000011
Patent Text Reader

Abstract

The invention provides a preparation method of doped zirconia electrolyte powder, an electrolyte supporting SOC unit prepared by using the powder and a process method. An improved coprecipitation method is adopted to solve the problem of component segregation caused by huge difference of solubility product constants of composite precipitates, and uniformly doped electrolyte powder is obtained. Meanwhile, the electrolyte powder is utilized, a hydrogen electrode coating and an electrolyte supporting body are subjected to multi-layer tape casting, co-sintering, isolation layer magnetron sputtering, oxygen electrode silk-screen printing and co-sintering again, the sintering process after coating deposition is simplified, the sintering frequency and the sintering time are reduced, and the unit breakage rate is reduced. The method is applied to the field of electrolyte supporting SOC units and electrolyte supporting SOC stacks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid oxide fuel cells (SOFCs) and solid oxide electrolyzers (SOECs), and in particular to electrolyte materials and electrolyte-supported SOC units and preparation methods, and is applicable to the fields of sheet-type SOC unit manufacturing and stacking, fuel cell power generation, and water electrolysis hydrogen production. Background Art

[0002] SOFC and SOEC often use zirconium oxide (ZrO2) based electrolyte materials. Pure phase ZrO2 has a monoclinic structure at room temperature and is generally doped with low-valent metal oxides to form a cubic phase structure. Currently, the most studied and commercialized doping materials are yttrium oxide (Y2O3) and scandium oxide (Sc2O3). Sc2O3 stabilized ZrO2 (ScSZ for short) can maintain a high ionic conductivity at 650~900℃.

[0003] In doped zirconia electrolyte materials, the Sc2O3 doping amount is generally controlled at 8~10mol%. When the doping amount is less than 8mol%, ScSZ is a mixture of tetragonal and cubic phases; when the doping amount is greater than 10mol%, ScSZ will have a rhombohedral phase. Impurity phases other than the cubic phase will affect its ionic conductivity. Currently, commercial products all use 10mol% Sc2O3 doping. The main reason for the complex phase structure of ScSZ is that Sc 3+ and Zr 4+ The ionic radius is similar, and a metastable phase is formed during high-temperature cubic phase annealing. This can be solved by doping a third phase stabilizer. Commonly used stabilizers include aluminum oxide (Al2O3), ytterbium oxide (Yb2O3), yttrium oxide (Y2O3) and cerium oxide (CeO2). Among them, Al 3+ Cannot enter the crystal lattice and can only exist as impurity Al2O3, Yb 3+ , Y 3+ and Ce 4+ It can enter the ZrO2 structure in the form of ions to form 8 ligands, which plays a role in stabilizing the phase structure. The amount of stabilizer is generally controlled at 0.5~2mol%, and the general structural formula is (Sc2O3) 0.10 (MO x ) y (ZrO2) 0.9-y , M is Yb, Y or Ce, x=1.5 or 2, y=0.005~0.02.

[0004] The co-precipitation method is a commonly used method for synthesizing powders in industry. It mainly involves dropping a mixed solution of two or more cationic raw materials and a precipitant into a mother liquor at a certain rate ratio to carry out a precipitation reaction to obtain precipitated particles. The target oxide is then obtained through washing, filtering, drying and calcining. For example, patents CN201210580238.7 and CN201710799934.X both use the co-precipitation method to synthesize scandium oxide-stabilized zirconia powder materials.

[0005] To synthesize (Sc2O3) 0.10 (CeO2) 0.01 (ZrO2) 0.89 For example, the solubility product constant of the precipitate Zr(OH)4 is 6.3×10 -49 , the solubility product constant of Sc(OH)3 is 7.94×10 -31 , the solubility product constant of Ce(OH)3 is 6.3×10 -22 The solubility product constants of cerium precipitate, zirconium precipitate and scandium precipitate are very different. To ensure that the three are in the precipitation environment at the same time, the pH value is generally 8~11, resulting in Zr 4+ and Sc 3+ Preferential and rapid precipitation, precipitate component segregation, and uneven stabilizer doping; the mass of each precipitate is calculated based on 1 mol of the target material. The mass of zirconium and scandium precipitates is 151.3g, and the mass of cerium precipitates is 1.9g. The mass ratio is ≈79:1. The subsequent solid-liquid mixing and solid-liquid separation processes cannot improve the component uniformity.

[0006] The electrolyte-supported SOC unit uses doped zirconia as a support, and has hydrogen electrode and oxygen electrode coatings prepared on both sides. It operates under medium-high temperature conditions of 650-900°C, and has broad application space in the fields of hydrogen production and power generation. The existing electrolyte-supported SOC unit preparation method mostly adopts a multiple sintering method, that is, the electrolyte support is sintered first, and then the hydrogen electrode, isolation layer and oxygen electrode are prepared separately, and sintered and solidified separately. This step-by-step sintering process is complex and costly, and it is easy to cause the unit to increase warping or even break during the multiple coating preparation and firing process. Summary of the invention

[0007] The task of the present invention is to overcome the deficiencies of the above technologies and provide a method for preparing a doped zirconium oxide electrolyte powder, and a method for preparing an electrolyte-supported SOC unit using the powder and a process method.

[0008] The present invention is accomplished by the following technical solutions: Preparation method of doped zirconium oxide electrolyte powder, the chemical formula of which is (Sc2O3) 0.10 (MO x ) y (ZrO2) 0.9-y, M is Yb, Y or Ce, x=1.5 or 2, y=0.005~0.02, and an improved coprecipitation method is used to deal with the component segregation problem caused by the huge difference in the solubility product constants of the composite precipitate. Elements with small solubility product constants such as scandium and zirconium are preferentially coprecipitated, and the third component dopant is dissolved in anhydrous ethanol and attached with an anchoring dispersant. The precipitate is mixed, dispersed, and aged in an ethanol solution, and then spray-dried and calcined to obtain a uniformly doped electrolyte powder.

[0009] An electrolyte-supported SOC unit and preparation method, a hydrogen electrode coating and an electrolyte support are multi-layered cast and co-sintered, a magnetron sputtering isolation layer and a screen-printed oxygen electrode are formed on the other side of the hydrogen electrode coating symmetrical to the electrolyte, and co-sintered to obtain an electrolyte-supported SOC unit.

[0010] Compared with the prior art, the present invention has the following advantages or effects: An improved co-precipitation method is used to improve the component segregation problem caused by the huge difference in the solubility product constants of the composite precipitates, and to obtain a uniformly doped electrolyte powder; in the preparation process of the electrolyte-supported SOC unit, the hydrogen electrode coating and the electrolyte support are multi-layered cast and co-sintered, the magnetron sputtering isolation layer and the screen-printed oxygen electrode are co-sintered again, which simplifies the sintering process after coating deposition, reduces the number of sintering times and sintering time, reduces the unit breakage rate, and has good process repeatability and strong reliability. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 The present invention is a schematic diagram of a process flow of a method for preparing doped zirconium oxide electrolyte powder.

[0012] The present invention is further described in detail below in conjunction with the accompanying drawings. DETAILED DESCRIPTION

[0013] Preparation method of doped zirconium oxide electrolyte powder, (Sc2O3) 0.10 (MO x ) y (ZrO2) 0.9-y ,M is Yb, Y or Ce, x=1.5 or 2, y=0.005~0.02, refer to Figure 1 : (1) Preparation of mixed solution A: Mix the zirconium source, the scandium source and deionized water to obtain a mixed solution A. (2) Precipitation reaction: Mix the precipitant with deionized water to obtain a mixed solution B, add it to the mixed solution A for precipitation reaction, adjust the pH value, and continue stirring for 3 to 6 hours to obtain a mixed solution of zirconium and scandium co-precipitate. (3) Washing and separation: Centrifuge and dehydrate the zirconium and scandium co-precipitate mixed solution obtained in step (2) to control the chloride ion content to less than 100 ppm, then wash with anhydrous ethanol and centrifuge, the number of alcohol washings ≥ 3 times, to obtain a zirconium and scandium co-precipitate. (4) Preparation of mixed solution C: Mix the M source, the anchoring dispersant and anhydrous ethanol to obtain a mixed solution C. (5) Mixing and aging: the zirconium and scandium precipitates obtained from P03 are added to the mixed solution C for mixing, dispersion and aging for 2 to 16 hours at a temperature of 20 to 50°C to obtain a uniform spray precursor mixture with a solid content of 15 to 65%. (6) Spray drying: the spray precursor mixture obtained from P05 is sent to a spray drying tower for spray drying to obtain a mixture of zirconium, scandium and M precipitation. The inlet temperature of the spray drying tower is set to 120 to 220°C, the outlet temperature is set to 55 to 85°C, and the protective gas is nitrogen. (7) Calcination: the spray-dried mixture is calcined at 950 to 1050°C for 2 to 5 hours to obtain (Sc2O3) 0.10 (MO x ) y (ZrO2) 0.9-y Electrolyte powder.

[0014] There is no specific requirement for the zirconium source and scandium source, as long as they can be ionized in water to produce corresponding cations, such as zirconium oxychloride hydrate, zirconium nitrate hydrate, acid-treated scandium oxide, hydrated scandium nitrate, hydrated scandium chloride, and the metal cation concentration in the mixed solution A is 0.5~5mol / L.

[0015] The precipitant is at least one of sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate, ammonium carbonate and organic amine, and the pH value is 7.8-9.6.

[0016] The M source is ytterbium salt, yttrium salt and cerium salt soluble in anhydrous ethanol, the anchoring dispersant is at least one of citric acid, tartaric acid, polyacrylic acid, hydrogen peroxide, monoethanolamine, diethanolamine, triethanolamine, ethylenediamine, ethylenediaminetetramethylenephosphonic acid, and octylphenol polyoxyethylene ether, and the mass ratio of M source to anchoring dispersant is: M source / anchoring dispersant = 1: 0.1~3.

[0017] Electrolyte supported SOC unit preparation: (1) Casting hydrogen electrode green sheets: mixing hydrogen electrode materials, organic solvents and auxiliary materials, grinding, filtering and degassing to form hydrogen electrode casting slurry, casting on PET film tape and drying, the drying conditions are 30-60°C for 2-3 hours to obtain hydrogen electrode green sheets. (2) Casting electrolyte green sheets on hydrogen electrode green sheets: mixing electrolyte materials, organic solvents and auxiliary materials, grinding, filtering and degassing to form electrolyte casting slurry, casting on hydrogen electrode green sheets obtained in step (1) and drying, the drying conditions are 30-150°C for 2-8 hours to obtain hydrogen electrode and electrolyte composite green sheets. (3) Cutting: cutting the composite green sheets obtained in step (2) into a certain size, the size is determined according to unit requirements and shrinkage rate, and no specific constraints and restrictions are imposed. (4) The first sintering, the cut composite green sheet is co-sintered at a high temperature of 1200~1400℃ for 1~4 hours to obtain an electrolyte-hydrogen electrode ceramic sheet. (5) Preparation of an isolation layer, in the electrolyte-hydrogen electrode ceramic sheet, the hydrogen electrode is symmetrical to the other side of the electrolyte by magnetron sputtering. (6) Preparation of an oxygen electrode, the oxygen electrode coating is prepared on the isolation layer by screen printing, the oxygen electrode material, organic solvent and auxiliary materials are mixed and ground to form an oxygen electrode slurry, screen printing is performed on the isolation layer, and drying is performed at 25~65℃ for 0.5~2 hours to obtain an oxygen electrode coating green sheet. (7) The second sintering, the ceramic sheet with oxygen electrode coating green sheet obtained by S06 is sintered at a high temperature of 900~1250℃ for 0.5~3 hours to obtain an electrolyte-supported SOC unit.

[0018] The thickness of the hydrogen electrode green sheet is 10-45 μm, the hydrogen electrode material is at least two of doped zirconium oxide, doped cerium oxide, metal nickel and nickel oxide, metal copper and copper oxide, metal platinum and platinum salt, metal palladium and palladium salt, and metal gold and gold salt, the organic solvent is at least two of methanol, anhydrous ethanol, toluene, xylene, isopropanol, acetone, butanone, ethyl acetate and butyl acetate, the auxiliary agent is at least one of polyvinyl butyral, acrylic resin, ethyl cellulose and methyl cellulose, dibutyl phthalate, dioctyl phthalate, oleic acid and cyclohexanone, the hydrogen electrode casting slurry has a solid content of 25-55% and a viscosity of 1000-3000 mPa·s, the doping element of the doped zirconium oxide is at least one of yttrium, scandium, ytterbium and cerium, and the doping element of the doped cerium oxide is gadolinium or samarium.

[0019] The composite green sheet has a thickness of 100-300 μm, and the electrolyte material is (Sc2O3) obtained from P07. 0.10 (MO x ) y (ZrO2) 0.9-y), M is Yb, Y or Ce, x=1.5 or 2, y=0.005-0.02, the organic solvent is at least two of methanol, anhydrous ethanol, toluene, xylene, isopropanol, acetone, butanone, ethyl acetate and butyl acetate, the auxiliary agent is at least one of polyvinyl butyral, acrylic resin, ethyl cellulose and methyl cellulose, dibutyl phthalate, dioctyl phthalate, oleic acid and cyclohexanone, the electrolyte casting slurry has a solid content of 30-75%, and a viscosity of 1500-15000 mPa·s.

[0020] The isolation layer material is a doped cerium oxide material, the doping element is gadolinium or samarium, the isolation layer thickness is 0.5~5μm, and the magnetron sputtering working conditions include: the sputtering power is 30~120W, the sputtering time is 0.5~5 hours; the working pressure is 0.5~1.5Pa, the deposition temperature is 50~750℃, the working gas is a mixture of argon and oxygen, and the volume ratio of argon to oxygen is 10:1~3; the sputtering target material is a doped cerium oxide target, a gadolinium-cerium alloy target or a samarium-cerium alloy target.

[0021] The thickness of the oxygen electrode is 10-50 μm, the oxygen electrode material is at least two of doped cerium oxide, lanthanum strontium cobalt iron, lanthanum strontium manganese, and lanthanum strontium cobalt, the organic solvent is at least one of ethanol, pine alcohol, tributyl citrate, ethyl acetate, butyl acetate, and butyl carbitol, and the auxiliary agent is at least one of polyvinyl butyral, polyvinyl alcohol, acrylic resin, ethyl cellulose and methyl cellulose, dibutyl phthalate, fish oil, castor oil, oleic acid, Span 80, graphite, carbon powder, polymethyl methacrylate, and starch. Example

[0022] Electrolyte powder synthesis, (Sc2O3) 0.10 (CeO2) 0.01 (ZrO2) 0.89 : (1) Preparation of mixed solution A: 2000g of zirconium oxychloride octahydrate, 105g of scandium chloride and 3000g of deionized water were mixed to obtain mixed solution A. (2) Precipitation reaction: 25% ammonia water was mixed with 5000g of deionized water, and the amount of ammonia water added was based on the pH value of 8.8±0.1 to obtain mixed solution B. Mixed solution B was added dropwise to mixed solution A under stirring to perform precipitation reaction. After the titration of mixed solution B was completed, stirring was continued for 3 hours to obtain a mixed solution of zirconium and scandium co-precipitate. (3) Washing and separation: centrifugal dehydration and washing, controlling the chloride ion content to <100ppm, then washing with anhydrous ethanol and centrifugal separation, repeating alcohol washing and separation 3 times to obtain a zirconium and scandium co-precipitate. (4) Preparation of mixed solution C: 26g of cerium chloride hydrate, 6g of ethylenediamine, 17g of octylphenol polyoxyethylene ether and 2000g of anhydrous ethanol were mixed to obtain a mixed solution C. (5) Mixing and aging: Add the zirconium and scandium precipitates into the mixed solution C for mixing, dispersing and aging, and continue stirring for 12 hours to obtain a spray precursor mixed solution. (6) Spray drying: Send the mixed solution to a spray drying tower for spray drying to obtain a mixture of zirconium, scandium and cerium. The inlet temperature of the spray drying tower is 150°C, the outlet temperature is 75°C, the protective gas is nitrogen, and the spray pressure is 0.1Mpa. (7) Calcination: Calcine the spray-dried mixture at 1000°C for 2.5 hours to obtain (Sc2O3) 0.10 (CeO2) 0.01 (ZrO2) 0.89 Electrolyte powder.

[0023] Three samples of the obtained electrolyte powder were randomly taken, each sample was 50g, and after sampling, they were mixed evenly by the quartering method. 5g of the sample was taken for X-ray fluorescence spectroscopy analysis. The results are shown in Table 1: project <![CDATA[ZrO2 (mass%)]]> <![CDATA[Sc2O3 (mass%)]]> <![CDATA[CeO2 (mass%)]]> <![CDATA[HfO2 (mass%)]]> <![CDATA[Al2O3 (mass%)]]> <![CDATA[SiO2 (mass%)]]> <![CDATA[Fe2O3 (mass%)]]> <![CDATA[Na2O (mass%)]]> Theoretical value 87.6100 11.0200 1.3700 0.0000 0.0000 0.0000 0.0000 0.0000 Sample 1 86.1688 10.8674 1.4750 1.3369 0.0081 0.0048 0.0127 0.0049 Sample 2 86.3189 10.7718 1.3950 1.2551 0.0073 0.0057 0.0165 0.0084 Sample 3 86.2936 10.6568 1.4133 1.3767 0.0089 0.0038 0.0102 0.0054

[0024] Electrolyte supported SOC unit preparation: (1) Cast hydrogen electrode embryo: 100g nickel oxide, 100g (Sc2O3) 0.10 (CeO2) 0.01 (ZrO2) 0.89 , 85g toluene, 85g isopropanol, 17g polyvinyl butyral, 5g dibutyl phthalate, 10g fish oil, 2g cyclohexanone were mixed, ground, filtered, and degassed to control the viscosity between 1500 and 2000 mPa·s to form a hydrogen electrode casting slurry, which was cast on a PET film tape with a casting thickness of 25μm and dried at 35°C for 2 hours to obtain a hydrogen electrode green sheet. (2) Casting electrolyte green sheets on hydrogen electrode green sheets: 1000g (Sc2O3) 0.10 (CeO2) 0.01 (ZrO2) 0.89, 300g toluene, 300g isopropanol, 85g polyvinyl butyral, 40g dibutyl phthalate, 50g fish oil, 8g cyclohexanone are mixed, ground, filtered, and degassed to control the viscosity between 7000 and 8000mPa·s to form an electrolyte casting slurry, which is cast on the hydrogen electrode green sheet with a casting thickness of 200μm and dried at 75°C for 3 hours to obtain a hydrogen electrode and electrolyte composite green sheet. (3) Cutting: Cut the composite green sheet obtained in step (2) into a size of 130mm×130mm. (4) First sintering: The cut composite green sheet is co-sintered at a high temperature of 1380°C for 2.5 hours to obtain an electrolyte-hydrogen electrode ceramic sheet. (5) Prepare the isolation layer, select the cerium-gadolinium alloy target material and use the magnetron sputtering method to prepare the isolation layer on the other side of the electrolyte-hydrogen electrode ceramic sheet where the hydrogen electrode is symmetrical to the electrolyte, and the deposition thickness is 1.5μm. The working conditions of the magnetron sputtering are: sputtering power is 80W, sputtering time is 2 hours; working pressure is 1Pa, deposition temperature is 300℃, and the volume ratio of working gas argon to oxygen is 10:2.5. (6) Prepare the oxygen electrode, grind and disperse 25g of lanthanum strontium manganese powder, 25g of gadolinium-doped cerium oxide, 4.0g of starch, 4g of ethyl cellulose, 25g of pine alcohol, 10g of butyl carbitol, 1.0g of fish oil, and 0.4g of Span 80 to form an oxygen electrode slurry, and screen print the slurry on the isolation layer to a thickness of 35μm, dry it at 55℃ for 2hr and dry it to obtain the oxygen electrode coating green body, the drying temperature is 25-65℃, and the drying time is 0.5~2 hours. (7) Second sintering: sintering the green ceramic sheet with oxygen electrode coating at 1150°C for 1.5 hours to obtain an electrolyte-supported SOC unit.

[0025] As described above, the present invention can be better implemented. The above embodiments are only the best implementation methods of the present invention, but the implementation methods of the present invention are not limited by the above embodiments. Other changes, modifications, replacements, combinations, and simplifications made without departing from the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing an electrolyte-supported SOC unit, characterized in that: The steps include: (1) Casting hydrogen electrode green sheets: mixing, grinding, filtering and degassing hydrogen electrode materials, organic solvents and auxiliary materials to form hydrogen electrode casting slurry with a solid content of 25-55% and a viscosity of 1000-3000 mPa·s, casting on PET film tape and drying to obtain hydrogen electrode green sheets. (2) Casting electrolyte green sheets on hydrogen electrode green sheets: mixing, grinding, filtering and degassing electrolyte materials, organic solvents and auxiliary materials to form electrolyte casting slurry with a solid content of 30-75% and a viscosity of 1500-15000 mPa·s, casting on hydrogen electrode green sheets and drying to obtain hydrogen electrode and electrolyte composite green sheets. (3) Cutting: cutting the obtained composite green sheets into a certain size. (4) First sintering: co-sintering the cut composite green sheets at a high temperature of 1200-1400°C for 1-4 hours to obtain electrolyte-hydrogen electrode ceramic sheets. (5) Preparation of an isolation layer: In the electrolyte-hydrogen electrode ceramic sheet, the isolation layer is prepared by magnetron sputtering on the other side of the electrolyte where the hydrogen electrode is symmetrical. (6) Preparation of an oxygen electrode: The oxygen electrode coating is prepared on the isolation layer by screen printing. The oxygen electrode material, organic solvent and auxiliary materials are mixed and ground to form an oxygen electrode slurry, which is screen printed on the isolation layer and dried. (7) Second sintering: The obtained ceramic sheet with the oxygen electrode coating is sintered at a high temperature of 900-1250°C for 0.5-3 hours to obtain an electrolyte-supported SOC unit.

2. The method for preparing an electrolyte-supported SOC unit according to claim 1, characterized in that: The hydrogen electrode green sheet has a thickness of 10-45 μm, and the hydrogen electrode material is at least two of doped zirconium oxide, doped cerium oxide, metal nickel and nickel oxide, metal copper and copper oxide, metal platinum and platinum salt, metal palladium and palladium salt, and metal gold and gold salt.

3. The method for preparing an electrolyte-supported SOC unit according to claim 1, characterized in that: The thickness of the hydrogen electrode and electrolyte composite green sheet is 100-300 μm, and the electrolyte material is doped zirconium oxide powder, and its chemical formula is (Sc2O3) 0.10 (MO x ) y (ZrO2) 0.9-y ), M is Yb, Y or Ce, x=1.5 or 2, y=0.005~0.

02.

4. The method for preparing an electrolyte-supported SOC unit according to claim 1, characterized in that: The isolation layer material is a doped cerium oxide material with a thickness of 0.5-5 μm. The isolation layer magnetron sputtering working conditions are: sputtering power is 30-120 W, sputtering time is 0.5-5 hours; working pressure is 0.5-1.5 Pa, deposition temperature is 50-750° C., working gas is a mixture of argon and oxygen, and the volume ratio of argon to oxygen is 10:1-3; sputtering target material is a doped cerium oxide target, a gadolinium-cerium alloy target or a samarium-cerium alloy target.

5. The method for preparing an electrolyte-supported SOC unit according to claim 1, characterized in that: The thickness of the oxygen electrode is 10-50 μm, and the material of the oxygen electrode is at least two of doped cerium oxide, lanthanum strontium cobalt iron, lanthanum strontium manganese, and lanthanum strontium cobalt.

6. The zirconium oxide-doped electrolyte powder according to claim 3, characterized in that: The preparation method comprises the following steps: (1) Preparation of mixed solution A: Mix the zirconium source, the scandium source and deionized water to obtain a mixed solution A with a metal cation concentration of 0.5~5 mol / L. (2) Precipitation reaction: Mix the precipitant with deionized water to obtain a mixed solution B, add it to the mixed solution A for precipitation reaction, adjust the pH value, and continue stirring to obtain a mixed solution of zirconium and scandium co-precipitate. (3) Washing and separation: Centrifuge and dehydrate the obtained zirconium and scandium co-precipitate mixed solution to control the chloride ion content to less than 100 ppm, then wash with anhydrous ethanol and centrifuge to obtain a zirconium and scandium co-precipitate. (4) Preparation of mixed solution C: Mix the M source, the anchoring dispersant and anhydrous ethanol to obtain a mixed solution C. (5) Mixing and aging: Add the obtained zirconium and scandium precipitates into the mixed solution C, perform mixing, dispersion and aging operations, and obtain a uniform spray precursor mixed solution with a solid content of 15~65%. (6) Spray drying: the obtained spray precursor mixture is sent to a spray drying tower for spray drying to obtain a mixture of zirconium, scandium and M precipitation. The inlet temperature of the spray drying tower is set to 120-220°C, the outlet temperature is set to 55-85°C, and the protective gas is nitrogen. (7) Calcination: the spray-dried mixture is calcined at 950-1050°C for 2-5 hours to obtain (Sc2O3) 0.10 (MO x ) y (ZrO2) 0.9-y Electrolyte powder.

7. The method for preparing doped zirconium oxide electrolyte powder according to claim 6, characterized in that: The precipitant is at least one of sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate, ammonium carbonate and organic amine, and the pH value is 7.8-9.

6.

8. The method for preparing doped zirconium oxide electrolyte powder according to claim 6, characterized in that: The M source is ytterbium salt, yttrium salt and cerium salt soluble in anhydrous ethanol, the anchoring dispersant is at least one of citric acid, tartaric acid, polyacrylic acid, hydrogen peroxide, monoethanolamine, diethanolamine, triethanolamine, ethylenediamine, ethylenediaminetetramethylenephosphonic acid, and octylphenol polyoxyethylene ether, and the mass ratio of M source to anchoring dispersant is: M source / anchoring dispersant = 1: 0.1~3.

9. Electrolyte supported SOC unit, characterized in that: The device is prepared by the preparation method according to any one of claims 1 to 8 and is applied to chip-type SOC stack modules, as well as in the fields of power generation and hydrogen production by water electrolysis.

Citation Information

Patent Citations

  • A scandium oxide-stabilized zirconium oxide solid solution and its preparation process

    CN103030392B

  • A scandium oxide-stabilized zirconium oxide and its preparation method

    CN107445203B

Cited By

  • Scandium-zirconium powder as well as preparation method and application thereof

    CN120441309A